Mengukur Indeks Kebahagiaan Mahasiswa IPB Menggunakan Analisis Faktor - Aulya Permatasari; Khairil Anwar Notodiputro; Kusman Sadik (Xplore: Journal of Statistics, 2018)
Undergraduate students of Bogor Agricultural University are spread out in 9 Faculties and 1 School. The difference of faculties and schools illustrate the different characteristics and burdens of student lectures on each faculty and school. This distinction raises various assumptions about the level of student happiness in every faculty and school. Student happiness analysis is measured using loading factor obtained from Factor Analysis. Based on the analysis, found that Faculty of Animal Science is the happiest faculty with happiness index reaching 66.88 and the lowest index of happiness found in the Faculty of Human Ecology with happiness index of 62.39.